STUDI PENGEMBANGAN USAHA PERKEBUNAN DI KABUPATEN KUTAI KARTANEGARA - Karmini Karmini (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The aim of this study was to know the development of plantation business in Kutai Kartanegara Regency.  Data were analyzed by using descriptive analysis.  Plantation business is managed by government-owned enterprise, private sector and farm small holder. The result of study showed the increase of plantation production in study area. Development of plantation should be continued to cultivate potential land.  Government shoud made the procedure of investment in Kutai Kartanegara Regency easier and faster for investors.